Nano cosmeceuticals: Emerging Advances, Therapeutic Benefits, Safety Concerns, and Regulatory Perspectives - Riddhi N. Patel; Vishwa N. Parmar; Bhavin D. Pandya; Kautuk P. Shah; Ajay K. Saluja; Shreyash A. Diwakar (Asian Journal of Pharmaceutical Research and Development, 2026)
Nanotechnology has revolutionized cosmetic and cosmeceutical formulations by enabling the development of advanced delivery systems with improved efficacy, stability, and consumer acceptance. Nano cosmetics and nano cosmeceuticals are increasingly used in products for skin, hair, nails, lips, and oral care, offering advantages such as enhanced penetration, targeted delivery, and better performance compared to conventional formulations. As a result, many traditional cosmetic products are being replaced by nano-based alternatives. However, concerns regarding the safety of nanomaterials, including increased skin penetration, potential toxicity, and environmental impact, have prompted the need for thorough evaluation and regulation. This review highlights the major nanotechnology-based delivery systems used in cosmetics, discusses recent patents, and examines their benefits and potential risks. It also provides an overview of the regulatory landscape governing cosmeceuticals, with a comparative analysis of regulations in India, Europe, and the United States. The review aims to support informed development, regulation, and responsible use of nano-enabled cosmetic products.